Existence and approximate controllability results for time-fractional stochastic Navier–Stokes equations - Chaudhary, Renu; Reich, Simeon; Nieto, Juan. J. (Nonlinear Analysis: Modelling and Control, 2026)
This paper deals with time-fractional stochastic Navier–Stokes equations, which are characterized by the coexistence of stochastic noise and a fractional power of the Laplacian. We establish sufficient conditions for the existence and approximate controllability of a unique mild solution to time-fractional stochastic Navier–Stokes equations. Using a fixed point technique, we first demonstrate the existence and uniqueness of a mild solution to the equation under consideration. We then establish approximate controllability results by using the concepts of fractional calculus, semigroup theory, functional analysis, and stochastic analysis.